The Transition and Spread of a Chaparral Crown Fire: Insights from Laboratory Scale Wind Tunnel Experiments. (20th July 2022) - Cobian-Iñiguez, Jeanette; Aminfar, Amir Hessam; Saha, Shusmita; Awayan, Kyle; Weise, David R.; Princevac, Marko
Abstract : Fire occurring in the chaparral behaves as a crown fire, a dual-layer fire that typically ignites in a dead surface fuel layer and transitions to an elevated live crown layer where it continues to spread. In chaparral fuels including chamise, a dominant species in southern California, flame transition to live crown fuels is associated with higher spread rates and greater fire intensity. Despite the relative importance of surface-to-crown transition and crown fire spread, most fire models represent chaparral fire as surface fire, therefore omitting key behavior processes driving this fire system. The purpose of this study was to characterize transition and spread behavior in chaparral fires modeled experimentally as crown fires. We examined heat release rate in the surface and crown fuel layers, time to transition, flame height, and rate of spread in wind-driven and nonwind-driven fires at two crown base heights. Our results showed that wind increased heat release rate, rate of spread, and flame height. A marked increase in heat release rate was observed in wind-driven fires, where adding wind produced an increase from 328 kW to 526 for a crown base height of 0.6 m and from 243 kW to 503 kW for a crown base height of 0.7 m. Further, crown base height served to decrease heat release rate and rate of spread for wind-driven and nonwind-driven fires.